FoodForCare: An Android application for self-care with healthy food - Natnicha Suthumchai (2018)
© 2016 IEEE. Recently, there are many people who ignore health concerns especially in their eating habits. This has made the number of diseases found in society, especially non-communicable diseases (NCDs) such as diabetes, hypertension, and cancer drastically increase every year. The number of patients having these diseases, could be reduced by paying more attention to the food that they eat and nutrition that they receive. Accordingly, the researchers would like to propose FoodForCare, an Android application for self-care with healthy food. The main purpose is to help users have better eating habits and a healthier lifestyle. FoodForCare provides functions for users to keep their daily personal health and food records of food intake. The users can see an analysis of nutrition and calories per day and whether it is sufficient or not. This application can give an overview on food calories and nutrition so that they can eat wisely. Finally, the development of this application hopes to help Thai people in order to manage their total nutrition and calories taken for a healthier lifestyle and will directly decrease the number of people who are getting diseases caused from a disorder of food and nutrition.